2023
DOI: 10.1096/fj.202201571r
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity‐induced alterations of the gut microbiota are BMI dependent

Abstract: Physical inactivity is one of the leading causes of chronic metabolic disease including obesity. Increasing physical activity (PA) has been shown to improve cardiometabolic and musculoskeletal health and to be associated with a distinct gut microbiota composition in trained athletes. However, the impact of PA on the gut microbiota is inconclusive for individuals performing PA in their day‐to‐day life. This study examined the role of PA and hand‐grip strength on gut microbiome composition in middle‐aged adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Moreover, Bifidobacterium could achieve emotional regulation through the brain-gut axis, showing a negative correlation with severe depression in mice [26,55]. Four studies in this review observed a significant difference between groups in Akkermansia [14,29,38,39], which has been previously described to have a high prevalence in the gut microbiome of athletes. It is noteworthy that the abundance of Akkermansia has been reported to inversely correlate with obesity and metabolic disorders in mice and humans (reference).…”
Section: Other Representative Bacteriamentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, Bifidobacterium could achieve emotional regulation through the brain-gut axis, showing a negative correlation with severe depression in mice [26,55]. Four studies in this review observed a significant difference between groups in Akkermansia [14,29,38,39], which has been previously described to have a high prevalence in the gut microbiome of athletes. It is noteworthy that the abundance of Akkermansia has been reported to inversely correlate with obesity and metabolic disorders in mice and humans (reference).…”
Section: Other Representative Bacteriamentioning
confidence: 61%
“…However, the dominant gut flora that was associated did increase after the exercise intervention. It is worth noting that greater alpha diversity of gut flora in adults is not always associated with gut health but might result from the growth of potentially harmful microbial [39,47]. Thus, it is important to explore biodiversity indices and interpret them in the context of specific GM composition changes.…”
Section: Changes In Microbial Diversity Indexmentioning
confidence: 99%
“…This is supported by recent findings showing individualized changes in the gut microbiota following ferrous sulfate supplementation in adults [ 18 ]. These differences are not only influenced by genetics [ 44 ], but also variation in daily routines including sleep and exercise [ 24 , 58 ]. Understanding how such factors impact the gut microbial response to iron supplementation requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included male, pregnant women, those on antibiotics (last 3 months), inflammatory disease, and cancer patients. Eligible participants underwent a battery of measures as previously reported [ 24 ]. Among all participants, 23 participants were identified as taking a low-level iron supplement, mainly in the form of a daily women’s specific multivitamin.…”
Section: Methodsmentioning
confidence: 99%
“…Participants answered questionnaires relating to demographics, lifestyle, diet, eating/drinking behaviors, smoking, medication, and sleeping habits as previously described. 19 Questionnaires were completed independently by the participants. Medication information was curated referring to DrugBank 20 and Drugs.com.…”
Section: ■ Methodsmentioning
confidence: 99%